A Study on Factors Affecting Entrepreneurship Development and Employment Growth (International Journal of Food and Nutritional Sciences, 2021)
Capital, labour, markets and raw materials, tariff policy and subsidies are the main economicfactors. Social factors can go a long way in promoting entrepreneurship. Entrepreneurial development is highlycorrelated with social attitudes, social status, social mobility, family background and education.Entrepreneurial environment is a collection of external conditions for entrepreneurs to engage inentrepreneurial activities including government policies, laws and regulations, socio-economic conditions,venture capital support, non-capital support and entrepreneurship and management skills. Apart fromeconomic, social, psychological and governmental, political factors, there are many other factors that affect theemergence and development of entrepreneurship.